the Pengembangan E-modul Pembelajaran Berbasis Google Sites Pada Mata Pelajaran Gambar Teknik Otomotif Kelas X di SMK Muhammadiyah Gamping: Pengembangan E-modul Pembelajaran Berbasis Google Sites Pada Mata Pelajaran Gambar Teknik Otomotif Kelas X di SMK Muhammadiyah Gamping - Adila Oktaviyani; Widodo Widodo (Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of this study was to design a Google Sites-based e-module for use in the Engineering Drawing class of SMK Muhammadiyah Gamping for tenth-grade students. Students had difficulty understanding the concept because the printed module was static, according to the needs analysis. This study used the 4D model, which stands for